Os deslocamentos forçados dos haitianos e suas implicações: um desafio global na sociedade de risco - Pinto, Joseane Mariele Schuck (Universidade do Vale do Rio dos Sinos, 2015)
Migratory movements coming from Haiti should be understood from the processes of structural situations and cyclical changes in the country. The reasons that make the country is characterized by loss of control of its territory for non-monopoly on the legitimate use of physical force within its borders, erosion of legitimate authority of the State to take collective decisions, the inability to provide public services adequate and to interact with other states as a full member of the international community, end up leaving it in a condition of frailty and vulnerability, is therefore imperative that your analysis. The issues of human mobility on the global stage, the object of study are supported by theoretical sociologists Ulrich Beck, Immanuel Wallerstein and Octavio Ianni, that portray the contemporary setting of the resulting set of changes brought about by globalization and the techno-scientific development, responsible for creating the risk society, as well as analysis of the world-system notions are references to characterize the landscape in which the phenomenon of migration takes on new meaning as one of the dimensions of global environmental change. Haiti is a result of society in which the social production of wealth is systematically accompanied by the social production of risks, coming to meet natural disasters, such as earthquakes, floods, hurricanes that make the country even more susceptible to shifts. Risks become involved and through social change and are the sociological basic concept to classify, interpret and organize social life. This context favors the emergence of thousands of forced displacement by natural disasters and by the progressive degradation of essential natural resources which seriously compromise the life and safety of people, making it impossible to survive in the affected locations. This new demand brings to the international scene the discussion about the ideal treatment to be used in relation to individuals and groups in situations of risk, for reasons that may or may not be related to conflict or persecution, and that may or may not cross borders of a state, and even if there is no uniformity on the concept of "environmental refugee", one can not deny the existence of a social problem to be faced. In this sense, the unveiling of the case of the forced displacement of Haitians, the understanding of this phenomenon and its implications in a global society of risk, will only be possible through research since the historical construction of the country in its political, economic, social and environmental. The origin of contemporary migration of Haitians, is not only grounded in the pursuit of economic improvements, as do economic migrants who move voluntarily, but that based on forced migration, marked by threats to life and livelihood, whether arising from natural causes or man-made (eg movements of refugees and internally displaced people as well as people displaced by natural or environmental, chemical or nuclear disasters, famine or development projects). Similarly, find out if these flows corroborate and how for the emergence of a new category of people: environmental refugees or environmental displaced, is necessary. The rest, it remains important to check all the ramifications of the choice of Brazil as migratory route of Haitians, given that demand for the country had high rise, which reached the mark of 50,000 at the end of 2014.
Keywords: Deslocado ambiental; Globalização; Haiti; Migração; Refugiado ambiental; Environmental moved; Globalization; Migration; Environmental refugee; ACCNPQ::Ciências Humanas::Sociologia